Technical and tactical readiness of the team "Helios" (Kharkiv) in the 26th Ukrainian soccer championship in the first league - Zhurid, S.; Dovbiy, O. (Slobozhanskyi herald of science and sport, 2018)
Purpose: to determine the model characteristics of the technical and tactical readiness of the team that participated in the Ukrainian championship of the first league in order to further improve and correct the training process.